Upper bound analysis and experimental investigations of dynamic effects during sinter-forging of irregular polygonal preforms - Singh S.; Jha A.K.; Kumar S. (My University, 2025)
The present paper investigates the effect of die velocity, i.e. dynamic effects on various deformation characteristics like flow of material, densification, strain rates, energy dissipations and die load during sinter-forging of irregular polygonal preforms. The expressions for exponential velocity fields, strain rates, energy dissipations and average die load have been established based on upper bound approach. The experiments have been conducted using compacted aluminium metal powder preforms to investigate their flow behavior. Based on the preform shape geometry and observed flow characteristics, it have been found that there was no velocity discontinuities or jumps across the common boundaries of small zones assumed over the surface of irregular polygonal preforms. To investigate the dynamic effects, two important parameters; energy and load factors have been introduced in the present study. The design of experiment (DOE) and response surface methodology (RSM) techniques have been used to demonstrate the interaction of various processing parameters on energy and load factors. The preform height reduction, relative density, axial strain rate and inertia energy dissipation were found to increase, where as die load was found to decrease with die velocity. The dynamic effects were found to be more pronounced during sinter-forging process at higher die velocities. It is expected that the present research work will be highly useful for understanding the dynamic effects during sinter-forging of complicate shape preforms, e.g. irregular polygonal shape. © 2007.